Values of Islam in The Local Wisdom of The Tomakaka Community of North Luwu, South Sulawesi - Purnamasari, Eka (State Islamic Institute of Palopo, 2024)
Cultural heritage in Indonesia, apart from having high historical value, is also closely linked to spiritual and religious values. However, in this modern era, local wisdom and customs are underestimated by millennials. Assumptions about ethnicity and culture that are even considered deviant from religious teachings. Culture is considered taboo and not worth preserving. Traditional habits that should become local wisdom are actually increasingly shifting and almost disappearing one by one. In this regard, the researcher intends to conduct research to review the religious values contained in the local wisdom of the Tomakaka people of North Luwu district, South Sulawesi. This is intended so that local wisdom as regional culture can continue and continue to exist in the onslaught of the modern world. The relationship between religious and cultural values is a complex and multidimensional subject. Religion is often a moral pillar in culture, shaping values, norms, and social institutions. However, culture also influences the way religion is practiced and interpreted in everyday life. Understanding this relationship is the key to embracing cultural and religious diversity throughout the world as well as the religious values contained in the local wisdom of the Tomakaka people of North Luwu, starting from the traditions of Toke' Sampa', Mapalesso Samaja, Massolo', Tudang Sipulung, and Ma'bunga ' Lalang..